13 A year of acute myocarditis in northern alberta. (15th May 2019) - Sonnex, Emer; Coulden, Richard
Abstract : Introduction: Acute myocarditis (AM) is a major cause of troponin positive chest pain in patients without obstructive coronary disease. Many cases relate to viral infection. Drug toxicity, alcohol and auto-immune diseases have also been implicated. Diagnosis is difficult and cardiac MR (CMR) can confirm/exclude the diagnosis. We reviewed all cases of suspected AM referred for CMR in 2017. Methods: Patients were identified from referral information recorded in the CMR daybook. All cases underwent pre- & post-contrast imaging to assess bi-ventricular function, myocardial oedema and late gadolinium enhancement (LGE). Results: Of 1753 adult patients undergoing CMR, 95 (5%) were for suspected myocarditis. 37 had no troponin rise or peak troponin I < 0.5µg/L (normal range ≤ 0.15µg/L). None of these had AM by MRI criteria (15 dilated cardiomyopathy, 1 pericarditis, 1 LV hypertrophy and 20 normal). Of the remaining 58, 31 showed edema and LGE typical of AM and 9 had non-ischemic LGE suggesting possible myocarditis. 9 patients had acute infarcts and 9 were normal. Seven of the normal patients had troponin I rise of <2 µg/L. Conclusion: Suspected acute myocarditis is a common indication for CMR. None of our cohort had a positive CMR for AM if troponin I was < 0.5µg/L. The demographics of positive cases mirrors previous series in terms of age and gender. Interestingly, the majority of positive AM cases had normal bi-ventricular function (26/40 or 65%). Longterm outcome of these patients has yet to be established and routine follow-up CMR may not be needed.